Didática da história e imagens: reflexões em torno da consciência histórica em visualidades formativas - Leal, Fernanda de Moura (2013)
This research seeks to contribute to the empirical reflections of History didactics by the investigation of historical consciousness, in formative visualities, from narratives produced by students, who graduated high school in the context of selective entrance examination vestibular for admission at Goias Federal University in 2011. The research is based on the imaging modality and its evaluative and formative potential, using them as a source to investigate historical awareness and skills in dealing with the images in historical studies. Women history makes itself present in the used cognition exercise, stressing the needs that were pointed out by Bergmann (1990) in reviewing the contents of history canons, reflecting on issues that are relevant to humans at the expense of conventional sources and themes. At first, research concepts that were used in the data analysis are pointed out, namely History didactics in German and Brazilian theory and experience, the concept of historical consciousness proposed by Jörn Rüsen (2001), History's guiding role, substantial and of-second-order concepts prepared by Peter Lee (2001) and the evidence concept. Then a study is made from the investigation of students historical ideas, being the source choice defined and justified, the research methodology presented, the grounded theory (GLASER and STRAUSS, 1967), and a vestibular exercise with images and gender theme used. In a third stage, the analysis of the expected answer and also the candidates' answers to the chosen question is made in order to compare the data with the presented theory in the first chapter.